2020
DOI: 10.1016/s2215-0366(20)30057-2
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and perinatal risk and protective factors for psychosis: a systematic review and meta-analysis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
3
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(189 citation statements)
references
References 84 publications
10
171
3
5
Order By: Relevance
“…Recent studies have focused on sex differences in psychopathologic outcomes associated with PS including anxiety, depression, ADHD, schizophrenia, and autism (Weinstock, 2001;Walsh et al, 2019;Davies et al, 2020;Scheinost et al, 2020). Chronic maternal stress was shown to increase anxiety-and depression-like behavior in prepubertal males relative to controls, whereas prepubertal females were less affected (Schulz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on sex differences in psychopathologic outcomes associated with PS including anxiety, depression, ADHD, schizophrenia, and autism (Weinstock, 2001;Walsh et al, 2019;Davies et al, 2020;Scheinost et al, 2020). Chronic maternal stress was shown to increase anxiety-and depression-like behavior in prepubertal males relative to controls, whereas prepubertal females were less affected (Schulz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genome wide association studies have also shown an increase in risk related to single nucleotide polymorphisms in oligodendrocyte specific genes ( 42 ). Furthermore, rodent models have shown that 2 nd trimester insults, especially maternal infection, a known risk factor for schizophrenia ( 43 ), can produce a decrease in fractional anisotropy (FA) in fronto-striatal-limbic circuitry similar to that seen in the illness ( 44 ). Supporting these discoveries, investigators have characterized white matter abnormalities in the CHR population.…”
Section: Structural Phenotypesmentioning
confidence: 99%
“…Inflammation has long been associated with the pathophysiology of schizophrenia ( 75 ). Winter births and maternal infections ( 43 ), genetic risk associated with the major histocompatibility complex ( 76 ), and subsequent discovery of the association of complement protein C4A ( 77 ) all represent converging evidence for the involvement of inflammation in the disease. Furthermore, in CHR subjects, several lines of evidence indicate increased inflammation prior to first episode psychosis.…”
Section: Inflammatory Phenotypesmentioning
confidence: 99%
“…Even if SSD and ASD are currently considered distinct entities, they both represent chronic, multi-factorial disorders. They share genetic predispositions [10,11] and environmental risk factors, such as complications during pregnancy or at birth [12,13]. Moreover, they present with similar neuroimaging patterns [14,15], neurochemical abnormalities, such as dopaminergic dysregulations [16,17], and inflammatory pathways [18].…”
Section: Introductionmentioning
confidence: 99%